Augustine's theology of preaching - Sanlon, Peter T. (Minneapolis Fortress Press, 2014)
Scholarship has painted many pictures of Augustine -- the philosophical theologian, the refuter of heresy, or contributor to doctrines like Original Sin -- but the picture of Augustine as preacher, says Sanlon, has been seriously neglected. When academics marginalize the Sermones ad Populum, the real Augustine is not presented accurately. In this study, Sanlon does more, however, than rehabilitate a neglected view of Augustine. How do the theological convictions that Augustine brought to his preaching challenge, sustain, or shape our work today? By presenting Augustine's thought on preaching to contemporary readers Sanlon contributes a major new piece to the ongoing reconsideration of preaching in the modern day, a consideration that is relevant to all branches of the twenty-first century church.
The historical context of Augustine's preaching -- Pagan oratory -- Training teachers : De doctrina christiana -- Interiority, temporality, and Scripture -- Case study : Riches and money -- Case study : Death and resurrection -- Case study : Relationships -- Conclusion.
Includes bibliographical references (pages 179-208) and index.
Keywords: Augustine, -- of Hippo, Saint, -- 354-430 -- Theology; Augustine, -- of Hippo, Saint, -- 354-430 -- Criticism and interpretation; Preaching; 276 =71 AUGUSTINUS -- Latijnse patrologie--AUGUSTINUS